Identifikasi Cendawan Endofit Menggunakan Teknik Polymerase Chain Reaction (Detection of Endophytic Fungi Using Polymerase Chain Reaction Technique) - Tuti Susanti Legiastuti; Tri Aminingsih (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Yellow leaf curl disease, caused by a member of Begomovirus (Geminiviridae), is one of important diseases of chilli pepper in Indonesia. Exploration of endophytic fungi was initiated in order to find biological control agents for an alternative control strategies of this disease. Isolates of endophytic fungi were collected from chilli pepper growing area in Sleman, Yogyakarta and further identification using molecular technique involving polymerase chain reaction (PCR) and DNA sequencing was performed. DNA fragments of ±500 bp were successfully amplified from 10 fungal isolates by PCR using primer pair ITS1/ITS4, but only 8 DNA sequences was obtained for further genetic analysis. Based on BLASTN analysis the endophytic fungi were identified as having the highest similarity with Pleosporaceae sp. (98%) for H1 isolate, Cercospora nicotianae (100%) for H5 isolate, ercospora piaropi (98%) for H11 isolate, Guignardia mangiferae (99%) for H16 isolate, Geomyces pannorum 95%) for H17 isolate, Diaporthe phaseoloru (99%) for H18 isolate, Dothideomycete sp. (100%) for K3 isolate, and Alternaria longissima (99%) for K10 isolate. Key words: Begomovirus, chillipepper, DNA sequencing, polymerase chain reaction